DEVELOPMENT OF UAV FUSELAGE USING BIOMIMETIC CONCEPTS BASED ON DRAGONFLY WING PATTERN: ENHANCING STRUCTURAL EFFICIENCY AND LIGHTWEIGHT DESIGN - Mohd Sufian, Nur Afiqah Izzati; Sahwee, Zulhilmy (Journal of Engineering and Technology (JET), 2024)
This research paper presents an invention that focuses on the application of biomimetic concepts based on the wing structure of dragonflies in the design and construction of UAV (Unmanned Aerial Vehicle) fuselages. The use of the structural and aerodynamic attributes exhibited by dragonfly wings structure into the design of UAV fuselage has the potential to enhance structural performance and yield a construction that is characterized by its low weight. This research encompasses a comprehensive analysis of the biological characteristics, structural composition, and aerodynamic properties of dragonfly wings. The effectiveness of the biomimetic-inspired UAV fuselage is determined through the utilization of SolidWorks and Ansys software. The results demonstrate the potential of incorporating biomimetic designs inspired by dragonfly wings into UAV technology, providing environmentally sustainable and lightweight alternatives for future aerial vehicles.